Comparison of infection risks and clinical outcomes in patients with and without SARS-CoV-2 lung infection under renin-angiotensin-aldosterone system blockade: systematic review and meta-analysis - Chu, Chang; Zeng, Shufei; Hasan, Ahmed A.; Hocher, Carl-Friedrich; Krämer, Bernhard; Hocher, Berthold (British journal of clinical pharmacology, 2021)
Aims Angiotensin-converting enzyme-2 (ACE2) is the receptor for SARS-CoV-2. Animal studies suggest that renin-angiotensin-aldosterone system (RAAS) blockers might increase the expression of ACE2 and potentially increase the risk of SARS-CoV-2 infection. Methods and Results The effect of ACE inhibitor (ACEI) treatment on the pneumonia incidence in non-COVID-19 patients (25 studies, 330 780 patients) was associated with a 26% reduction of pneumonia risk (odds ratio [OR]: 0.74, P < .001). Pneumonia-related death cases in ACEI-treated non-COVID-19 patients were reduced by 27% (OR: 0.73, P = .004). However, angiotensin II receptor blockers (ARB) treatment (10 studies, 275 621 non-COVID-19 patients) did not alter pneumonia risk in patients. Pneumonia-related death cases in ARB-treated non-COVID-19 patients was analysed only in 1 study and was significantly reduced (OR, 0.47; 95% confidence interval, 0.30 to 0.72). Results from 11 studies (8.4 million patients) showed that the risk of getting infected with the SARS-CoV-2 virus was reduced by 13% (OR: 0.87, P = .014) in patients treated with ACEI, whereas analysis from 10 studies (8.4 million patients) treated with ARBs showed no effect (OR, 0.92, P = .354). Results from 34 studies in 67 644 COVID-19 patients showed that RAAS blockade reduces all-cause mortality by 24% (OR = 0.76, P = .04). Conclusion ACEIs reduce the risk of getting infected with the SARS-CoV-2 virus. Blocking the RAAS may decrease all-cause mortality in COVID-19 patients. ACEIs also reduce the risk of non-COVID pneumonia. All-cause mortality due to non-COVID pneumonia is reduced by ACEI and potentially by ARBs.